2021
DOI: 10.1016/j.thromres.2021.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Brain-derived extracellular vesicles mediated coagulopathy, inflammation and apoptosis after sepsis

Abstract: The activation of coagulation, inflammation and other pathways is the basic response of the host to infection in sepsis, but this response also causes damage to the host. Brain-derived extracellular vesicles (BDEVs) have been reported to cause a hypercoagulable state that can rapidly develop into consumptive coagulopathy, which is consistent with the pathophysiological process of sepsis-induced coagulopathy. However, the role of BDEVs in sepsis-induced coagulopathy remains unclear. Materials and methods: Male … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…It has been demonstrated that traumatic brain injury in mice caused a release of EVs from microglia, while injection of these EVs into a healthy mouse brain led to neuroinflammation [ 184 ]. Intrastriatal injection of brain-derived EVs has been reported to activate microglia and stimulate the release of pro-inflammatory mediators; therefore, EVs could act locally to exacerbate central inflammation after initial injury [ 185 ]. Of note, it has been demonstrated that after stroke [ 186 ] and TBI [ 187 , 188 ], an increased number of circulating EVs had the potential to induce systemic immune reaction [ 186 , 188 ], indicating EV-mediated brain–immune system communication.…”
Section: Biology Of Extracellular Vesiclesmentioning
confidence: 99%
“…It has been demonstrated that traumatic brain injury in mice caused a release of EVs from microglia, while injection of these EVs into a healthy mouse brain led to neuroinflammation [ 184 ]. Intrastriatal injection of brain-derived EVs has been reported to activate microglia and stimulate the release of pro-inflammatory mediators; therefore, EVs could act locally to exacerbate central inflammation after initial injury [ 185 ]. Of note, it has been demonstrated that after stroke [ 186 ] and TBI [ 187 , 188 ], an increased number of circulating EVs had the potential to induce systemic immune reaction [ 186 , 188 ], indicating EV-mediated brain–immune system communication.…”
Section: Biology Of Extracellular Vesiclesmentioning
confidence: 99%
“…This increase is not consistent with the fact that ATF3 expression is repressed by miR-494, and urinary miR-494 was elevated during AKI (97,98); however, the finding that miRNAs contribute to the determination of extracellular vesicle release and intracellular retention (108) may be the key to clarifying the relationship between miR-494 and exosomal ATF3. Lin et al demonstrated the functional effect of brain-derived extracellular vesicles (mainly from neurons and astrocytes) on kidney tissue in sepsis; treatment with brain-derived extracellular vesicles exacerbated sepsis-induced injury and apoptosis in the kidney of rats (109). Moreover, Seibold et al suggested that extracellular vesicles secreted on thorax trauma are strongly associated with sepsis and biochemical markers of AKI (110).…”
Section: Inflammationmentioning
confidence: 99%
“…The primary sources of plasma EVs released during sepsis are platelets and circulating immune cells, such as macrophages, dendritic cells, neutrophilic granulocytes, and natural killer cells ( 54 , 55 ). However, recent studies have found that EVs released from the astrocytes and perhaps neurons could possibly contribute to sepsis-related complications ( 56 ). Lin et al measured expression of glial fibrillary acidic protein (GFAP) and neuron-specific enolase in plasma EVs.…”
Section: Extracellular Vesicles As Mediators In Traumamentioning
confidence: 99%